Predictors of Intraoperative Echocardiography: Analysis of The Society of Thoracic Surgeons Database - MacKay, Emily J; Zhang, Bo; Shah, Ronak M; Augoustides, John G; Groeneveld, Peter W; Desai, Nimesh D (The Annals of thoracic surgery, 2023)
Intraoperative transesophageal echocardiography (TEE) is associated with improved outcomes after cardiac surgery, but unexplained practice pattern variation exists. This study aimed to identify and quantify the predictors of intraoperative TEE use among patients undergoing isolated coronary artery bypass graft surgery (CABG) or cardiac valve surgery. This observational cohort study used The Society of Thoracic Surgeon (STS) Adult Cardiac Surgery Database data to identify and quantify the predictors of intraoperative TEE use among adult patients aged 18 years or more undergoing either isolated CABG or open cardiac valve repair or replacement surgery between January 1, 2011, and December 31, 2019. Generalized linear mixed models were used to measure the relationship between intraoperative TEE and patient characteristics, surgical volume, and geographic location, while accounting for clustering within hospitals (primary analysis) or surgeons (secondary analysis). Of 1,973,655 patients, 1,365,708 underwent isolated CABG and 607,947 underwent cardiac valve surgery. Overall, intraoperative TEE was used in 62% of surgeries. The primary hospital-level generalized linear mixed models analysis demonstrated that the strongest predictor of intraoperative TEE use was the hospital where the surgery occurred-with a median odds ratio for TEE of 10.13 in isolated CABG and 5.30 in cardiac valve surgery. The secondary surgeon-level generalized linear mixed models analysis demonstrated similar findings. Intraoperative TEE use (vs lack of use) during surgery was more strongly associated with hospital and surgeon practice patterns than with any patient-level factor, surgical volume, or geographic location.